Past, present and future the idea of human rights - Agudelo Ramírez, Martín (2017)
The following article refers to a brief but concise history of human rights. This review from the natural law of Western acient era to our present times that we are doing, aims not only to review the history regarding this issue, but submit to criticism some of its postulates and make the reader reflect on the real path we should be in order to strengthen or reconsider the main objective of human rights.